1992
DOI: 10.1007/bf00183253
|View full text |Cite
|
Sign up to set email alerts
|

Production of cellulase and xylanase by a wild strain of Trichoderma viride

Abstract: The production of cellulase and xylanase was investigated with a newly isolated strain of Trichoderma viride BT 2169. The medium composition was optimized on a shake-flask scale using the Graeco-Latin square technique. The temperature and time for optimal growth and production of the enzymes in shake cultures were optimized using a central composite design. The temperature optima for maximal production • of filter paper cellulase (FPase), xylanase and fl-gluosidase were 32.8 °, 34.7 ° and 31.1 ° C, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 25 publications
3
33
0
1
Order By: Relevance
“…Similarly, in other studies carried out with Trichoderma sp. it was concluded that the optimum temperature varied between 45 and 60°C (Dekker, 1983;Gomes et al, 1992). Besides, for fungal xylanases the optimum temperature was 60°C (Chandra and Chandra, 1995;Chandra and Chandra, 1996;Gandhi et al, 1994).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, in other studies carried out with Trichoderma sp. it was concluded that the optimum temperature varied between 45 and 60°C (Dekker, 1983;Gomes et al, 1992). Besides, for fungal xylanases the optimum temperature was 60°C (Chandra and Chandra, 1995;Chandra and Chandra, 1996;Gandhi et al, 1994).…”
Section: Discussionmentioning
confidence: 97%
“…Our studies revealed that the xylanase activity was maximum around pH 5. In studies carried out with Trichoderma sp., it was also concluded that the most suitable pH value for xylanase activity was 5 (Dekker, 1983;Gomes et al, 1992;Royer and Nakkas, 1991). The optimum pH was also around 5 in similar experiments on fungal xylanases (Milagres et al, 1993;Gandhi et al, 1994;Sigoillot et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of various Trichoderma spp. to produce xylanases on various lignocellulosics has been reported (7,19,20,22). This paper presents the potential of a local soil isolate of Trichoderma viride (S 34), to produce xylanase on various feed stuffs like wheat straw, maize straw, bajra straw, oat hay, barseem hay and jowar straw under submerged fermentation conditions (SmF).…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus, Gliocladium, Schizophyllum and Trichoderma, are not thermostable at 50°C or above, the hydrolytic efficiencies of these enzymes are low (Dekker and Richards 1976;Gomes et al 1989Gomes et al , 1992Poutanen 1988;Senior et al 1989;Steiner et al 1987). Moreover, all these fungi produce appreciable amounts of cellulase activity.…”
Section: Introductionmentioning
confidence: 99%